(untitled) (World Economics and Finance Bulletin, 2023)
The research aims to explain the role and importance of the external auditor in reviewing the internal control in the electronic accounting systems with regard to each of the requirements of the information technology of the control environment in the internal control system, the requirements of the information technology of risk assessment in the internal control system, the requirements of the control activities technology in the internal control system, and the requirements of Information technology of the communication and information process in the internal control system, and information technology requirements of the control process in the internal control system. The research was applied to a sample of individuals working in the Bureau of Financial Supervision, who are the external auditors who audit the accounts of government units during the year 2022. The research reached a set of conclusions, the most important of which was that the quality of the software used in computerizing accounting information systems has an effective role in improving the internal control system, and that computerizing accounting information systems makes data available in the hands of investment decision makers in record time to make investment decisions successful decisions. And keeping pace with market changes, and that this will increase the efficiency of the external auditing apparatus and thus improve the quality of the reports it provides because the computerized software is characterized by impartiality, it made investment decision makers trust the outputs of the computerized accounting system